Soil and water chemistry and mobilization rates for phosphate, dissolved organic matter and methane from soil cores of rewetted peatlands in northeast Germany - Dominik Zak; Tobias Goldhammer; Alvaro Cabezas; Jörg Gelbrecht; Robert Gurke; Carola Wagner; Hendrik Reuter; Jürgen Augustin; Agata Klimkowska; Robert McInnes (PANGAEA, 2017)
Long-term drainage and intensive agricultural use of peatlands make it unlikely that the original sink functions for nutrients and carbon as well as low-nutrient conditions can be re-established within a human time perspective. The data presented here consists of i) soil characteristics, ii) water quality, and iii) mobilization rates for phosphate, dissolved organic matter and methane from soil cores of altogether 12 rewetted inundated peatlands. In addition we included data from a rewetted non-inundated peatland ("Lehstseemoor"). All studied sites are representative of calcareous rich, i.e. groundwater charged peatlands (= fens) found in the lowlands of NE Germany, as well as in other parts of Europe such as Great Britain, the Netherlands or Poland. All sites developed as fens with peat forming small-sedge-brown moss plant communities in their central parts, with sedge and reed stands at the margins, and occurring either at the edge of areas of mineral soils or close to a water course. Approx. 300 years ago the sites were drained for peat excavation or agriculture. The study sites extquotesingle climate is continental, with a mean annual precipitation of 582-596 mm. The mean daily temperature is 0.7-1.2 °C in January and 18.1-19.1 °C in July (mean of 1991-2007 from the nearby meteorological stations at extquotesingleDeutscher Wetterdienst extquotesingle). Field measurements and an incubation experiment in the laboratory were performed to study the effect of top soil removal on: i) soil and water quality; ii) P mobilisation from soil to porewater; iii) net fluxes of P and dissolved organic matter at the soil-surface water interface; and iv) potential methane production.
Supplement to: Zak, D et al. (2018): Top soil removal reduces water pollution from phosphorus and dissolved organic matter and lowers methane emissions from rewetted peatlands. Journal of Applied Ecology, 55(1), 311-320, https://doi.org/10.1111/1365-2664.12931